Banana resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Musadoc 1999, INIBAP. ISBN 2 9108 10348 INIBAP Parc scientifique Agropolis 2 34397 Montpellier Cedex France Fax: + 33 467 610 334 Email: inibap@cgiar.org